Correlations between 3D animation test score, spatial ability and computer experiences amongst multimedia major university students / Sharkawi Che Din - Che Din, Sharkawi (Institute of Graduate Studies, UiTM, 2013)
Deficits in spatial abilities, particularly Spatial Visualization and Spatial Rotation affect the performance of 3D Computer Animation among Multimedia major university students. Lacking of necessary spatial ability factors may affect students’ performance in 3D Computer Animation. Some students experienced greater difficulties in performing a complicated visualization task required in creating three-dimensional (3D) objects and animation. The purpose of this study was to examine the relationship between Spatial Ability, Computer Experiences and the 3D Computer Animation performance among Multimedia major undergraduate students at Malaysian public university. In addition, this study also examined whether Spatial Ability could be used to predict students’ performance in 3D Computer animation course. Specifically the study attempted, 1) to investigate the correlation between Spatial Rotation test score and students’ performance in 3D Computer Animation test score among multimedia major undergraduate students, 2) to investigate the correlation between Spatial Visualization test score and students’ performance in 3D Computer Animation test score among multimedia major undergraduate students, 3) to investigate the correlation between Computer Understanding and Experience Scale (CUE) and performance in 3D Computer Animation course among multimedia major undergraduate students, 4) to determine whether Spatial Ability is the possible predictors of successful performance of 3D Computer Animation course among multimedia major undergraduate students and, 5) to examine significant differences between Spatial Ability test score and a CUE test score based on demographics with their performance in 3D Computer Animation…